Political communication: a multidisciplinary study from social sciences - Restrepo-Echavarría, Néstor Julián (2019)
The aim of this paper is to describe the study of Political Com- munication historiographically, showing its theoretical evolution. Political communication involves thinking of a discipline that has several theoretical approaches and schools of thought that, from the social sciences, politics, communication and sociology, have contributed to the construction of po- litical communication as a new academic discipline. Therefore, this paper seeks to contribute to the current discussions on the origin, definitions and approaches to analysis on political communication, which for many is con- sidered an illegitimate and trivial discipline, but which at the moment is in the center of the study of modern democracies from the remarkable crisis of political representation and political disaffection, the lack of political ideolo- gies and high personalization and especially the new forms of communicative interaction between citizens and governments.